Legal Analysis of the Position of Exoneration Clause in the Contract Legal System in Indonesia - Danial Syah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
The development of social life and human interaction methods results in changes in the nature of laws. The forms of agreements or contracts in the early stages of human life were characterized by strong emotional ties. Written contracts were merely created as a reminder of their previous contractual relationships, not necessarily to bind parties to an agreement. However, as society's interactions expanded to reach the external world beyond their domicile, humans began to consider how to engage in contracts without being disadvantaged, especially by parties providing facilities, such as financing or other services, who held greater bargaining power than others. This led to the creation of pre-prepared contract documents without the consent of the other party, which is known as the "exoneration clause." According to the law, the existence of standard contracts containing an exoneration clause may render the agreement void if it fails to meet the requirements of a valid agreement, unless the contents of the contract are explained beforehand and the second party accepts the presence of the contract. The inclusion of an exoneration clause in a standard contract, as seen from the conditions for a valid agreement under Article 1320 of the Civil Code, may lead to the nullification of the agreement due to a lack of mutual consent caused by one party's exploitation of the other party's situation in determining the contract's content. Meanwhile, from the perspective of Consumer Protection Law Number 8 of 1999, standard contracts containing an exoneration clause (liability waiver) are legally void.